Competitive purposefulness - O. V. Mikhailov (Вестник университета, 2019)
The insufficiences of the targeting the majority of the firms of the world economy and connected with it management problems have been allocated. The diff rences in the contents and formulation of the vision mission and purposes in the contemporary competitive environment have been shown. A particular importance of the content and correct target setting in the global competition has been highlighted. Сriteria and stages of target setting and extraordinary advantages of the competitive purposefulness for the companies and society have been disclosed on examples.